2010
DOI: 10.1097/psy.0b013e3181f0bc1c
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Loneliness and Proangiogenic Cytokines in Newly Diagnosed Tumors of Colon and Rectum

Abstract: The results of this study suggest VEGF to be an angiogenic mechanism through which loneliness may lead to worse cancer-related outcomes. Implications are discussed in terms of devising targeted psychosocial and immunotherapeutic interventions for cancer patients with low social support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 36 publications
2
34
0
1
Order By: Relevance
“…VEGF expression in tumor specimens taken from chronically stressed mice was significantly higher compared to control mice further correlating psychosocial conditions with tumor biology [16]. In colon cancer patients, implicit loneliness measured on a validated questionnaire correlated with significantly higher levels of VEGF by immunohistochemistry assessment of tumor specimens [25]. High levels of circulating interleukin 6 (IL-6), a pro-inflammatory cytokine, in patients with ovarian cancer have been associated with poor survival and earlier disease progression [26], and research has shown that ovarian cancer patients with low levels of social attachment have significantly higher levels of IL-6 [27].…”
Section: Discussionmentioning
confidence: 93%
“…VEGF expression in tumor specimens taken from chronically stressed mice was significantly higher compared to control mice further correlating psychosocial conditions with tumor biology [16]. In colon cancer patients, implicit loneliness measured on a validated questionnaire correlated with significantly higher levels of VEGF by immunohistochemistry assessment of tumor specimens [25]. High levels of circulating interleukin 6 (IL-6), a pro-inflammatory cytokine, in patients with ovarian cancer have been associated with poor survival and earlier disease progression [26], and research has shown that ovarian cancer patients with low levels of social attachment have significantly higher levels of IL-6 [27].…”
Section: Discussionmentioning
confidence: 93%
“…Further research on the mechanisms underlying this relationship showed that lack of social support (or high levels of subjective loneliness) can translate into psychosocial stress, which then alters the endocrine and immune systems (17). In conclusion, assisting social support with organizational support and establishment of some type of screening for psychological distress in patients may lead to better cancer-related outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…General psychometric properties of IAT methodology across applications are reviewed by Nosek et al (2007). The IAT-L has shown good internal consistency and predictive validity, having been associated with greater cardiovascular reactivity to stress in a nonclinical sample (Nausheen et al, 2007) and with higher angiogenic cytokine activity in colorectal cancer patients (Nausheen et al, 2010). …”
Section: Methodsmentioning
confidence: 99%